Cranial Reconstruction Using Antibiotic-Impregnated Calcium Phosphate Bone Cement With a Titanium Mesh Sheet. Issue 5 (July 2020) - Ogino, Akihiro; Nakamichi, Miho; Takeda, Kei; Onishi, Kiyoshi
Abstract : Background: The authors treated skin ulcer accompanied by cranial osteomyelitis using a combination of antibiotic-impregnated calcium phosphate bone cement (Biopex; Pentax, Tokyo, Japan) and a titanium mesh sheet (3D Mesh Plate; Bear Medic, Tokyo, Japan). Method: A 71-year-old male was treated with superficial temporal artery-middle cerebral artery bypass surgery for diffuse cerebral infarction and obstruction of the left internal carotid artery by a previous doctor. Skin necrosis and epidural abscess developed in the sutured region after surgery, and ulcer accompanied by temporal bone exposure remained. Thus, the patient transferred to our department. A bone defect formed by debridement and sequestrectomy was measured at 4.5 × 8 cm (30 cm 2 ). Methicillin-resistant Staphylococcus aureus was detected on wound culture test. Cranioplasty with a combination of calcium phosphate bone cement impregnated with teicoplanin, to which the causative bacteria showed high sensitivity, and a titanium mesh sheet and scalp reconstruction with a free rectus abdominis musculocutaneous flap were performed. Results: As of 6 months after surgery, no infection has relapsed and no complication, such as resorption of the calcium phosphate bone cement and breakage of the titanium mesh sheet, was noted on postoperative computed tomography. Conclusion: The authors performed cranial reconstruction with a combination of teicoplanin-impregnated calcium phosphate bone cement and a titanium mesh sheet in a patient with Methicillin-resistant Staphylococcus aureus infection-induced skin ulcer accompanied by cranial osteomyelitis and achieved subsidence of infection. Drug-impregnated calcium phosphate bone cement has a problem with strength, but combination with a titanium mesh sheet as an auxiliary support material enables application to relatively extensive cranial full-thickness defects and it may be a useful treatment method.